Composition And Structur Of Vegetaon In The Dere Black Monkey (Macaca maura schienz 1825) In Lejja nature park, Soppeng District - Liana Liana; Witno witno (Jurnal Penelitian Kehutanan BONITA, 2022)
This study discusses the composition of the type and structure of vegetation in the habitat of the black dare monkey (Macaca Maura) at the Lejja Nature Tourism Park, Soppeng Regency, which aims to determine the composition of the type and structure of the vegetation and habitat of Macaca Maura in the Lejja Nature Tourism Park. The research is located in the Lejja Nature Tourism Park Conservation forest area, Soppeng Regency. The method used is observation, purposive sampling, literature study, and documentation. At the same time, the Pole level found 12 species with a total of 35 individuals and 12 families. And Sapling found 17 species with a total of 69 individuals with 17 families. At the same time, the Semai level found 20 species with a total of 50 individuals with 20 families. The Angsana tree and the highest LBDS at the tree and pole levels, with a value of 9040.69%, while the lowest is owned by the Campenong tree, with a value of 92.85%. Meanwhile, for the highest sapling level of plant species, the Arungganga tree has an LBDS value of 393, 69%, while the lowest LBDS value is owned by Locong-Locong with a value of 13.19%.Â Â